Romance and Revolution: The Immigrant Experience of Emma Goldman - Laytner, Anson (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2024)
Much has been written concerning Emma Goldman: one of America’s foremost anarchists, a leader in the struggle for free speech and a pioneering supporter of birth control and women's liberation. She was a critic not only of American political, economic, and social structures, but also brave enough to condemn the repressive tactics of the Bolshevik regime of Vladimir Lenin and Leon Trotsky. However, little has been written about Emma Goldman's experience as a Russian-Jewish immigrant woman in the United States. This is a significant omission, for it was this experience of hers, as recorded in her autobiography Living My Life, which provided the crucible in which Emma Goldman was transformed into the notable woman she became. Through a close reading of her autobiography, this essay will document her transformation from a young immigrant woman struggling to understand society and personal relationships to becoming an independent, self-confident woman, an anarchist revolutionary leader, and a mature citizen of the world.